New Approach for Investigating Diffusion Kinetics Within Capacitive Deionization Electrodes Using Electrochemical Impedance Spectroscopy - Lenz, Magdalena; Zabel, Jana; Franzreb, Matthias (Frontiers in Materials, 2020)
Capacitive deionization (CDI) has become an important research topic in terms of water purification as it is a cost-and energy efficient approach for the desalination of brackish water. Carbon-based materials are often used as electrodes in this process due to a variety of morphologies and their suitable performance in this field. In recent studies it was already shown that a conscientiously chosen set of electrode properties has an enormous effect on the performance behavior of CDI cells. However, most of the studies focus on the optimization of the electrosorption capacity, while the question on how material properties influence the kinetic behavior of a CDI setup has been less intensively studied so far. Here we show that the kinetic effects of electrode materials can be studied in great detail by using electrochemical impedance spectroscopy (EIS). EIS studies of CDI electrodes have been reported before, however, in contrast to these we introduce a method of presenting and analyzing EIS results. This is especially suitable for extracting the frequency ranges in which different rate limiting mechanisms dominate. The new Nyquist Incline Frequency plot (NIF) shows the local slope of the Nyquist plot in dependency of the applied frequency. By this, electron transfer and mass transfer mechanisms which show a characteristic slope in the classical Nyquist plot can be directly visualized together with the information in which time domain they occur. The data derived from the new EIS plot show a clear correlation to pore size distributions from BET measurements, as well as effective capacities and electrosorption kinetics, extracted from CDI experiments. Therefore, we think that by using the NIF plot electrode materials for CDI processes can be conveniently characterized and compared within a single diagram, helping to standardize CDI material development.